Obesity: a key component of psoriasis - Correia, Bernardo; Torres, Tiago (Acta Biomedica Atenei Parmensis, 2015)
Psoriasis has been associated with several cardiometabolic comorbidities as well as clinically significant increased risk of cardiovascular disease and mortality. Obesity seems to have a key role in linking psoriasis and cardiovascular disease. There are a growing number of epidemiological studies associating psoriasis and obesity. The mechanism responsible for this association is not certain, but it is probably multifactorial, involving genetic, environmental and immune-mediated factors. Nonetheless, the chronic inflammatory state associated with obesity appears to be a key component of this relationship. Obesity is, therefore, a major factor in the management of psoriatic patients, with implications in treatment efficacy and safety. Moreover, weight loss has been shown to have a positive effect on psoriasis severity and response to treatment. The aim of this review is to synthesize the current evidence on the association between psoriasis and obesity, exploring the physiopathological mechanisms that link both diseases and highlighting the importance of obesity control in the efficacy and safety of systemic treatment of psoriasis. All clinicians must be aware of this association, so they can recognize it and provide the patients a proper follow-up and multidisciplinary approach when needed.